Spatiotemporal Analysis of Linear Skating Sprint in Male and Female Bandy Players: Analysis of Acceleration and Maximal Speed Phase - Roland van den Tillaar; Haris Pojskic; Håkan Andersson (Biomechanics)
Background/Objectives: This study aimed to investigate the skating determinants and differences between male and female bandy players in the spatiotemporal variables during acceleration and maximum sprint skating velocity. Methods: Seventy-four female bandy players (age: 18.9 ± 4.1 years; height: 1.67 ± 0.06 m; body mass: 63.2 ± 7.4 kg; training experience: 13.4 ± 3.9 yrs.; and 26 elite and 48 junior elite) and 111 male bandy players (age: 20.7 ± 5.0 years; height: 1.80 ± 0.05 m; body mass: 76.4 ± 8.4 kg; training experience: 13.8 ± 5.0 yrs.; and 47 elite and 66 junior elite players) performed linear sprint skating over 80 m. Split times were measured every ten metres by photocells to calculate velocities for each step and spatiotemporal skating variables (glide times and length, step length, and frequency) by IMUs attached to the skates. The first six steps (acceleration phase), the six steps at the highest velocity (maximal speed phase), and the average of all steps were used for analysing glide-by-glide spatiotemporal variables. Results: These revealed that male players exhibited higher acceleration and maximal skating velocity than female players. A higher acceleration in men was accompanied by shorter gliding time, longer step length, and higher step frequency. When skating at maximal speed, male players had a longer step length and gliding time and length. The sub-group analysis revealed that step frequency did not correlate with skating velocity, acceleration, or maximal speed phases. On the other hand, glide and step lengths significantly correlated with skating velocity in both phases (r ≥ 0.60). Conclusions: In general, for faster skating in bandy, it is generally better to prioritise glide and step length than stride frequency. Hence, players should be encouraged to stay low and have more knee flexion to enable a longer extension length and, therefore, a longer path and more horizontal direction of applied force to enhance their acceleration ability.